2018
DOI: 10.1002/cjce.23131
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous production of phycobiliproteins and carbonic anhydrase by Spirulina platensis LEB‐52

Abstract: The simultaneous production of carbonic anhydrase and the phycobiliproteins, C-phycocyanin and allophycocyanin, was evaluated during the cultivation of Spirulina platensis using Zarrouk's medium in its non-diluted (100 % ZM) and diluted to 20 % (v/v) (20 % ZM) forms. In both media, Spirulina simultaneously produced carbonic anhydrase and phycobiliproteins. For the phycobiliproteins' production, higher concentrations (mg/g) of C-phycocyanin and allophycocyanin were obtained when 100 % ZM was used. For carbonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…1a). A similar result was found in previous studies in which it was demonstrated that biomass production was unchanged in nitrogen-deficient medium compared to Zarrouk medium at low light, while protein production and C-PC content were decreased (Olguín et al 2001;Sala et al 2018). When A. platensis was cultivated at high light, growth increased and resulted in a higher nitrogen demand.…”
Section: Discussionsupporting
confidence: 90%
“…1a). A similar result was found in previous studies in which it was demonstrated that biomass production was unchanged in nitrogen-deficient medium compared to Zarrouk medium at low light, while protein production and C-PC content were decreased (Olguín et al 2001;Sala et al 2018). When A. platensis was cultivated at high light, growth increased and resulted in a higher nitrogen demand.…”
Section: Discussionsupporting
confidence: 90%
“…Zarrouk medium was used for inoculation, cultivation, and maintenance of the cyanobacterium . Cultivation was performed on discontinuous mode using a photobioreactor (Erlenmeyer flask), where 20% (v/v) of inoculum (initial concentration of 0.75 g/L) was added . Temperature, agitation/aeration, and light were performed according to Ores et al Cells were recovered by filtration through a cellulose acetate membrane and destined for the cell pretreatment step and subsequent extraction process.…”
Section: Methodsmentioning
confidence: 99%
“…In the control assay (Assay 4), wet biomass (equivalent to 5 mg of dry biomass) was resuspended directly in 10 mL of TRIS‐SO 4 buffer and UAE was carried out using a Sonic Ruptor 250 (Omni International Inc., Kennesaw, GA) with frequency of 20 kHz (potency of 60 W). During UAE, samples were kept at 4 °C and the extraction process took 12 min . All experiments were performed in triplicate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spirulina platensis LEB-52 was cultivated in Zarrouk medium according to Sala et al (2018). The biomass was recovered by filtration and resuspended in EDTA diluted in Tris-SO4 buffer (50 mmol·L -1 , pH 7.4), with a biomass concentration of 1.5 mgbiomass·mL -1 .…”
Section: Methodsmentioning
confidence: 99%